RhoGEF17, a Rho-specific guanine nucleotide exchange factor activated by phosphorylation via cyclic GMP-dependent kinase Iα - Lutz, Susanne; Mohl, Marion; Rauch, Julia; Weber, Pamina; Wieland, Thomas (Stem cells, 2013)
RhoGEF17, the product of the ARHGEF17 gene, is a Rho-specific guanine nucleotide exchange factor (GEF) with an unusual structure and so far unknown function. In order to get insights in its regulation, we studied a variety of signaling pathways for activation of recombinantly expressed RhoGEF17. We found that in the presence of stable cGMP analogs RhoGEF17 associates with and is phosphorylated by co-expressed cGKIα at distinct phosphorylation sites leading to a cooperative activation of RhoA, the Rho dependent kinases (ROCK) and serum response factor-induced gene transcription. Activation of protein kinase A did not induce phosphorylation of RhoGEF17 nor altered its activity. Furthermore, we obtained evidence for a ROCK-driven positive feedback mechanism involving serine/threonine protein phosphatases, which further enhanced cGMP/cGKIα-induced RhoGEF17 activation. By using mutants of RhoA which are phosphorylation resistant to cGK or mimic phosphorylation at serine 188, we could show that RhoGEF17 is able to activate RhoA independently of its phosphorylation state. Together with the ROCK-enforced activation of RhoGEF17 by cGMP/cGKIα, this might explain why expression of RhoGEF17 switches the inhibitory effect of cGMP/cGKIα on serum-induced RhoA activation into a stimulatory one. We conclude that RhoGEF17, depending on its expression profile and level, might drastically alter the effect of cGMP/cGK involving signaling pathways on RhoA-activated downstream effectors.
Available online 27 November 2012
Gesehen am 29.06.2018